2014
DOI: 10.1186/1756-3305-7-346
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardiness and biochemical response to low temperature of the unfed bush tick Haemaphysalis longicornis (Acari: Ixodidae)

Abstract: BackgroundThe survival of overwintering ticks, is critical for their subsequent population dynamics in the spring, and consequent transmission of tick-borne diseases. Survival is largely influenced by the severity of the winter temperatures and their degree of cold hardiness at the overwintering stage. The bush tick Haemaphysalis longicornis, is widely distributed in China, and can transmit various pathogens that pose serious medical/veterinary problems. In the present study we investigated the effect of low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 37 publications
1
42
2
1
Order By: Relevance
“…Third, this tick has a large distribution, including northern China and the Russian territories of Primorsky Krai, where it was documented to be able to overwinter despite cold temperatures and snow cover (Zheng et al, 2011). Prior literature indicates that while it is susceptible to freezing temperatures, this tick is able to acclimate to cold temperatures, increasing their glycerol and protein content (Yu et al, 2014). Finally, given that we have documented evidence that Haemaphysalis longicornis can overwinter in the counties where it was detected on the Atlantic coast, where we know there is frost and snow cover above these environmental criteria, it would seem counterintuitive to include these in our adopted rule-based climate envelope model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this tick has a large distribution, including northern China and the Russian territories of Primorsky Krai, where it was documented to be able to overwinter despite cold temperatures and snow cover (Zheng et al, 2011). Prior literature indicates that while it is susceptible to freezing temperatures, this tick is able to acclimate to cold temperatures, increasing their glycerol and protein content (Yu et al, 2014). Finally, given that we have documented evidence that Haemaphysalis longicornis can overwinter in the counties where it was detected on the Atlantic coast, where we know there is frost and snow cover above these environmental criteria, it would seem counterintuitive to include these in our adopted rule-based climate envelope model.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature indicates that while it is susceptible to freezing temperatures, this tick is able to acclimatmean either air or ground frost at various levels. Third, Lawrence et al (2017) has shown in their sensitive to cold temperatures, increasing their glycerol and protein content (Yu et al, 2014). Finally, given that we have documented evidence that Haemaphysalis longicornis can overwinter in the counties where it was detected on the Atlantic coast, where we know there is frost and snow cover above these environmental criteria, it would seem counterintuitive to include these in our adopted rulebased climate envelope model.…”
Section: Discussionmentioning
confidence: 99%
“…Preferential temperature ranges of ticks was between 15°C and 25°C with the exception of D. variabilis , which displayed a higher proportion of ticks at 12°C. The lowered temperature preference in D. variabilis could be a higher tolerance to colder temperatures (Rosendale et al, 2016b; Yu et al, 2014) or an impaired ability to detect temperatures. Importantly, is unlikely that D. variabilis was immobilized by the lower temperature since activity was noted as low as 10°C.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous freezing and direct chilling were not considered significant mortality factors in the field but inoculative freezing: ice nucleation around organic or inorganic entities (Costanzo and Lee 2013) is an important cause of overwintering mortality, following 2 h at − 5 and − 3 °C in direct contact with ice (Burks et al 1996). Haemaphysalis longicornis is freeze susceptible (Yu et al 2014) and gradual exposure to low temperatures can enhance its cold hardiness, while the possible formation of cryoprotective proteins is suggested, but not proven. Stewart et al (1998) found that adults of A. americanum did not undergo behavioural diapause when winter-exposed.…”
Section: Prediction Variablesmentioning
confidence: 99%